Judgement Sebagai Sistem Appraisal dalam Iklan Kecantikan Visual Media Cetak - Riris Tiani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
This papper investigated the appraisal system used in the verbal message advertisements visual beauty of each print media. Verbal message visual beauty of each print media were analyzed using appraisal theory which found on domain: attitude. Attitude as negotiating meaning to answer research problems. Judgement as the appraisal which dominate the verbal message advertisement visual beauty of the print media. This study is qualitative and interpretative in which the data analyzed using analysys of appraisal framework to identify categoriez of calusses the establish verbal message advertisement visual beauty of print media. The result showed thet category of clauses that building message advertisement visual beauty of print media dominated by appraisal tool that dominates moral judgement with direct, positive character as a praise and negative character as criticism.